KORELASIPERSEPSISISWATENTANGKEMAMPUANMENGAJAR GURUDENGANHASILBELAJAR SOSIOLOGISISWAKELASXI - Graevina Aulelia Oroh; Amrazi Zakso; Rustiyarso Rustiyarso (Universitas Tanjungpura, 2021)
AbstractTheresearchtitleis